KKN Kolaboratif 080 Jember: Literasi Digital, Edukasi Public Speaking, dan Sosialisasi Pola Hidup Sehat di Desa Sukamakmur: indonesia - Destiawan, Rian Anggia; Maulina Arianta, Citra Oriza; Putra, Fahad Dwi Maulana; Nafila, Amanda Eka Putri; Hasanudin, Muhammad Nur; Sa’diah, Halimatus; Wibowo, Mahmud Lucky; Aziz, Habibatul; Khofifah, Siti Nur; Wikoyah, Nur Uli; Kusdianti, Eriza; Putri, Disa Alfia (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2025)
Community service serves as a concrete way for academic partnerships to meet local demands by empowering the community. The Collaborative Community Service Program (KKN) in Sukamakmur Village, located in Ajung Subdistrict, was implemented with an emphasis on digital skills, public speaking training, and health awareness initiatives. The primary goal was to boost the abilities of local residents and elementary school pupils in using digital tools for product promotion, enhancing their public speaking abilities, and encouraging early understanding of healthy lifestyles. The strategies used involved educational sessions, guidance, engaging social interactions, and practical experiences. The outcomes show that the community learned how to set up marketplace accounts and understood the significance of business legitimacy through NIB registration and halal certification. At the same time, elementary school students gained confidence in their public speaking and discovered healthy lifestyle habits through learning activities and juice-making workshops. Furthermore, the CERDAS program effectively incorporated environmental education, physical activity, and student creativity. In summary, this community service initiative greatly contributed to improving digital literacy, cultivating soft skills, and raising health awareness, as well as fostering environmental consciousness among the residents of Sukamakmur Village.